THE EFFECT OF ESTAFET WRITING TECHNIQUE ON WRITING RECOUNT TEXT - Muliadi, Mul; Rahman, Khalqir; Rizal, Samsul; Azhar, Azhar (LPPM Institut Pendidikan Nusantara Global, 2023)
This research is intended to investigate the effect of Estafet Writing Technique on writing Recount Text at XI Grade Students of SMA IT Dhiaul Fikri. The problems in writing Recount Text were: 1) The students have lack in vocabulary, 2) The students are difficult to start writing 3) The students are difficult to comprehend the tenses 4) the teacher does not have various techniques in teaching writing. The research formulations of the problem were: is there the effect of Estafet writing technique in improving students’ writing skill in recount text and to what extent is the effect of Estafet writing technique to students’ writing skill at SMA IT Dhiaul Fikri. The purpose of this research was to know the effect of Estafet writing technique in improving students’ writing skill and to know extent the effect of Estafet writing technique to students’ writing skill at SMA IT Dhiaul Fikri. This research uses an experimental quantitative method with pre-test and post-test design. The data were collected through pre-test and post-test in essay test form and analyzed by using t-test formula. The result of the research showed that the mean score of post-tests was 78.50 and mean score of pre-tests was 54.00. So, there was significant effect of using estafet writing technique toward students’ writing recount text at the 11th grade of SMA IT Dhiaul Fikri.